Evaluation of the Relationship between Knowledge Level and Anxiety Level of Cancer Patients with Port Catheter - Buse Sekmen; Anita Karaca (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: Complications related to port catheterization can be prevented or reduced in patients who are informed about port catheterization, and they can also experience less anxiety and fear.Aim: This study was conducted to evaluate the relationship between the level of knowledge about port catheterization and the level of anxiety in cancer patients with port catheters, and to determine the factors affecting it.Method: The sample of this descriptive and correlation study consisted of 136 patients receiving chemotherapy. The data was collected by the Patient Information Survey, Port Catheterization Patient Information Survey, and the Beck Anxiety Inventory.Results: Of the patients, 15.4% received training before port catheterization and the physician gave 9.6% of the training. The total mean scores of both scales were determined 20.12 ± 2.44 for the Port Catheterization Patient Information Survey and 8.17 ± 4.85 for the Beck Anxiety Inventory. In the study, the married patients’ port catheterization knowledge mean score was found to be statistically higher than that of the single patients, and the difference was significant (p lt; 0.05). In addition, this study found no significant relationship between port catheterization knowledge and anxiety scores (r = 0.13; p gt; 0.05).Conclusion: The patients' knowledge level about port catheterization was above average and their anxiety level was mild. The level of knowledge of the patients about port catheterization did not affect their anxiety levels. Nurses need to consider individual characteristics and disease-related variables in the education of patients with port catheters